Tinjauan Historis Mengenai Pelibatan Sektor Keamanan Dalam Krisis Kesehatan - Nashir , Asep Kamaluddin; Sukmawan, Denny Indra (Jurnal Keamanan Nasional, 2022)
Security sector engagement, in particular TNI, Polri, and BIN are seen as dominant during the Covid-19 pandemic. It triggered concern across the public, as the civil argued that their security approach was ineffective. On the other hand, their involvement is guaranteed by the laws and regulations. Best practices across the world show that the involvement of the security sector in dealing with pandemics is a necessity, especially for countries that have poor national health systems. This study uses qualitative methods, with secondary data.